Investigating the effect of the heavy metals cadmium, chromium and lead, alone and in combination on an endothelial cell line - Oberholzer, Hester Magdalena (University of Pretoria, 2023)
Dissertation (MA (Anatomy))--University of Pretoria, 2022.